Hadith about the Prophet's Diet - Maftuhah Syam; Mujiyo Mujiyo (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to discuss the hadith perspective on the diet of the Prophet Muhammad. This research is a qualitative type by applying literature study to interpret the hadith about the diet of the Prophet Muhammad with a content analysis approach. The results and discussion of this study include the understanding of diet, how the concept of a healthy diet in religion and health, and how the concept of the Prophet's diet in the hadith. This study concludes that maintaining a diet is very important for daily life because food is a stimulant for the growth of brain cells, improves function, improves memory and concentration. This includes physical and spiritual cleanliness and environmental cleanliness. This study recommends all parties to maintain their diet, if the eating or drinking pattern is good and healthy, then the body will be healthy and have the stamina in carrying out daily activities